Rebuilding vascular access: from the viewpoint of mechanics and materials - Battistella, Aurora; Linger, Morgan; Nguyen, Anh Thy; Madukwe, David; Roy-Chaudhury, Prabir; Tan, Wei (Frontiers in Bioengineering and Biotechnology, 2024)
This review presents a comprehensive analysis of vascular access in hemodialysis, focusing on the current modalities, their associated challenges, and recent technological advancements. It closely examines the status of three primary types of vascular access: arteriovenous fistulas, arteriovenous grafts, and central venous catheters. The review delves into the complications and pathologies associated with these access types, emphasizing the mechanobiology-related pathogenesis of arteriovenous access. Furthermore, it explores recent clinical trials, biomaterials, and device innovations, highlighting novel pharmaceutical approaches, advanced materials, device designs, and cutting-edge technologies aimed at enhancing the efficacy, safety, and longevity of vascular access in hemodialysis. This synthesis of current knowledge and emerging trends underscores the dynamic evolution of vascular access strategies and their critical role in improving patient care in hemodialysis.